Safety of routing protocols in ad hoc networks and possible attacks in the network - Stefanović, Radiša Radomir; Pavlović, Boban Zoran (Vojnotehnički glasnik / Military Technical Courier, 2013)
This paper describes an ad hoc network, specific for its mobility, more abruptness and self-organization. Because of their properties, routing protocols in ad hoc networks must be adapted to applications and satisfy safety requirements - confidentiality, integrity and availability. These are the characteristics and challenges for the development of protocols to counter attacks, especially in military applications. Some of the known attacks are described and one of the methods for safety testing routing protocols is listed.   Introduction Ad hoc networks are temporary networks established for some particular purpose. Participants in the network – stations, entities (entrances and exits) from the network- move, create new and terminate the old connection. Without the infrastructure and central management, they need to find information about the neighboring nodes and to manage communication. Due to the growing need for communication in areas where there is no infrastructure, such as site accidents, fires, floods, agricultural land, and certainly for the army, the number of wireless devices is increasing. Communication based on the principle anywhere and anytime is in demand. In this paper, the focus will be on ad hoc networks for military purposes. This network must be able to transmit tactical information in the presence of enemy attack, which requires an answer to the question of security protocols in ad hoc networks. Certainly, the development of the Internet and wireless communications has led to rapid development of malicious procedures intended to unauthorized access to information, communications jamming and disabling or changing data in the personal interest. Specifics of ad hoc networks Wireless ad hoc networks are dynamic self-organizing networks of peer nodes (Omidyar, 2000). They are formed without planning, without any infrastructure and each node is equally involved in traffic forwarding. In addition to sending information, they act as a host which has to transmit the control data from/to other nodes. the routing process dynamically adapts to the network status as it changes, in accordance with changing position or termination/arrival of new nodes. Since the communication is based on wireless connection, there is a problem of noise attenuation and interference. As it is previously mentioned, all this requires the selected protocols that can cope with these challenges. Ad hoc networks are characterized by: mobility, abruptness, decentralization and self-organization. Regarding their application, these networks are divided into mobile ad hoc networks MANET, access networks (mesh) and sensor networks.   MANET routing algorithm in networks   Efficient routing is one of the main issues that has to be resolved in an ad hoc network architecture (Tipper, et al, 2002), and (Trivedi, 2001). Mobile networks are divided into three groups of routing  protocols: proactive or table-driven, reactive or protocols on request (on-demand) and hybrid protocols, whose main characteristics are given in Table 1. In proactive routing protocols, the route to a destination is determined as soon as the node joins the network and will be held during the times of periodic renewal (routing table is updated each time). In reactive protocols, routing is done by sending the appropriate data. When a node wants to send data to the destination, if there is no available link, the protocol starts the process of finding a path towards the destination. Hybrid routing protocols combine the above modes. Routing security in ad hoc networks   Security of information transfer generally requires fulfilling the three most important security requirements. These are: confidentiality, integrity and availability.     The attacks in ad hoc networks Because of the open medium transmission, the wireless network is vulnerable to various attacks,  the most important including: • Flooding • Sleep deprivation • Black Holes • Distribution network • Wormhole • The rush • Detection of the location • The invisible node To maintain a desired efficiency in terms of attack, routing protocol must be able to find the correct paths and failures to disclose them. In other words, protocols must provide path detection and successful submission of data. Conclusion Establishing a network connection and a successful data transmission is an important feature of any communication network. Unlike wired and wireless infrastructure networks, ad hoc networks are characterized by greater mobility, abruptness and self-organization. Because of the specificity, the need for the development of protocols designed particularly for ad hoc networks has developed. For special purposes, as military requirements are, designing the protocol takes into account safety as one of the most important requirements. In military air systems, security systems with zero tolerance for error must be used. There are several methods for safety testing of routing protocols, and the network simulation is often applied. The combination of different methods increases the success of test performances.
Keywords: security; protocols; Ad hoc networks